Plethysmographic Peripheral Perfusion Index: Could It Be a New Vital Sign? - Elshal, Mamdouh M.; Hasanin, Ahmed M.; Mostafa, Maha; Gamal, Reham M. (Frontiers in Medicine, 2021)
Plethysmograpgic peripheral perfusion index (PPI) is a very useful parameter with various emerging utilities in medical practice. Peripheral perfusion index represents the ratio between pulsatile and non-pulsatile portions in peripheral circulation and is mainly affected by two main determinants: cardiac output and balance between sympathetic and parasympathetic nervous systems. Peripheral perfusion index decreases in cases of sympathetic predominance and/or low cardiac output states; therefore, it is a useful predictor of patient outcomes in critical care units. Peripheral perfusion index could be a surrogate for the cardiac output in tests for fluid responsiveness, as an objective measure of pain especially in un-cooperative patients and as a predictor of successful weaning from mechanical ventilation. Being simple to measure, easy to interpret and continuously displayed real-time variable make the PPI a convenient parameter for detecting the adequacy of blood flow and sympathetic-parasympathetic balance